Influencia de los medios de comunicación en la conducta humana de los estudiantes de la Unidad Educativa Los Guayacanes cantón Quevedo, año 2022 - Calderón Defaz, Lilian Mercedes (2022)
Given the technological boom, the media offer different types of entertainment competing with each other with the sole intention of capturing the public, but entertainment content does not always have a rating suitable for all audiences, many of the programming they offer through their digital platforms do not contain a positive message, presenting programs of a violent nature, misleading advertising, misrepresentation of information, journalistic tabloids and sensationalism, nude images influencing the behavior of people who consider what is transmitted by the media to be normal. Through this research, the influence of the media is addressed, in the behavior of the students of the Los Guayacanes Educational Unit, the purpose is to provide information on the quality of content they watch and the effects that these produce in their development and integration with society.